La sabana arbolada "El Escobio", Liberia, Guanacaste, Costa Rica - Elizondo Castillo, Luis H. (1988)
An ecological study of a tree savanna was conducted at “El Escobio”, Liberia, Guanacaste, Costa Rica. The site shows a seasonal climate; with well defined dry and wet seasons. Soils are poor on nutrients, favouring a dominant coverage of herbaceous plants (Cyperaceae and Graminae) more or less xeromorphic, and the growth of some scattered tree species.A great number of rare and economically important species were found at the riparian forest. This forest plays a significative role in keeping a diverse fauna, due to the variety of fruits and flowers available throughout the year.